2019
DOI: 10.1371/journal.pone.0226328
|View full text |Cite
|
Sign up to set email alerts
|

Human perception and biosignal-based identification of posed and spontaneous smiles

Abstract: Facial expressions are behavioural cues that represent an affective state. Because of this, they are an unobtrusive alternative to affective self-report. The perceptual identification of facial expressions can be performed automatically with technological assistance. Once the facial expressions have been identified, the interpretation is usually left to a field expert. However, facial expressions do not always represent the felt affect; they can also be a communication tool. Therefore, facial expression measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 93 publications
0
14
0
Order By: Relevance
“…This device can detect the contractions of facial muscles related to smiling-the orbicularis oculi and zygomaticus major. These facial muscle areas have been researched with EMG sensors to measure specific smiles that show spontaneous and positive emotions (Frank et al, 1993;Mauss and Robinson, 2009;Johnson et al, 2010;Perusquía-Hernández et al, 2019). Compared to other physiological sensors, such as electroencephalography and functional MRI, facial EMG can be attached directly to the facial muscles involved in smiling (Maria et al, 2019).…”
Section: Apparatusmentioning
confidence: 99%
“…This device can detect the contractions of facial muscles related to smiling-the orbicularis oculi and zygomaticus major. These facial muscle areas have been researched with EMG sensors to measure specific smiles that show spontaneous and positive emotions (Frank et al, 1993;Mauss and Robinson, 2009;Johnson et al, 2010;Perusquía-Hernández et al, 2019). Compared to other physiological sensors, such as electroencephalography and functional MRI, facial EMG can be attached directly to the facial muscles involved in smiling (Maria et al, 2019).…”
Section: Apparatusmentioning
confidence: 99%
“…First, system accuracy when targeting one facial stimulus does not guarantee accuracy when targeting another facial stimulus, i.e., their generalizability across various domains is unproven. The interest in affective studies has shifted from posed and static facial images to more spontaneous and dynamic facial movements [ 12 , 13 , 14 , 15 ]. In this situation, the most important question for affective computing systems is “to what extent does the automatic AU detection system generalize to other data in the various domains.” To the best of our knowledge, how well open-source AU detection systems and even commercial AU detection software can perform with spontaneous and dynamic facial movements compared to human FACS coding remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, posed or polite facial expressions might differ depending on cultural background (Thibault, Gosselin, Brunel, & Hess, 2009;Thibault, Levesque, Gosselin, & Hess, 2012) and racial match (Hourihan, Benjamin, & Liu, 2012;Meissner & Brigham, 2001). Only few studies targeted participants with mixed cultural and ethnic backgrounds (Cohn et al, 2004;Perusquía-Hernández, Ayabe-Kanamura, & Suzuki, 2019a). Future research should embrace diversity, as this is likely to play a factor in the generalisation of automatic recognition.…”
Section: Methodological Assumptions Unresolved Issues and Open Quesmentioning
confidence: 99%
“…Despite the ambiguous definition of smile offsets and temporal units, it is possible to observe a familiar shape in several studies (Cohn & Schmidt, 2004;Jarlier et al, 2011;Mavadati et al, 2016;Perusquía-Hernández, Ayabe-Kanamura, & Suzuki, 2019a;Perusquía-Hernández et al, 2017b;Saito et al, 2020;Schmidt et al, 2006). Moreover, different studies have shown that when posing a smile for the camera, or under instruction, the decay of the smile is sharper than that of spontaneous smiles of enjoyment (Perusquía-Hernández, Ayabe-Kanamura, & Suzuki, 2019a;Perusquía-Hernández et al, 2017b;Saito et al, 2020). This might be the most distinct feature of posed smiles elicited in this manner, and it seems easy to distinguish given the high accuracy of several detection systems.…”
Section: The Shape Of a Smilementioning
confidence: 99%